The Issue of “Women's Literature” in Contemporary Chinese Literature: Creators of Style and A Wide Range of Themes - Miadovna, Nazirova Shukriya (International Journal of Psychosocial Rehabilitation, 2020)
This article addresses the emergence of women's literature has been the subject of much research in world literary studies. The main reason is that many women artists have been involved in the literature of a particular nation at a particular time. In China, the concept of “women's literature” is officially included in the scientific issue. So far, few studies on Chinese women literature have been published. The emergence of literature in this area is inextricably linked to China's political life and socio-cultural environment, which has laid the groundwork for a later stage in the history of literature. Without studying this stage of literary history, it is difficult to get a complete picture of the development of modern Chinese literature, particularly of women's literature. The research also emphasizes the influence of historical period on literature and the fate of its representatives.